Menafsir Ulang Keberagamaan Umat Beragama - Firdaus M Yunus (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Freedom in interpreting religion will boost the creation of peaceful and tolerant of life “condition” with other religions within plurality of religion. Inclusivism to convey religious meanings will be taken seriously and a must within plurality of religion. Understanding and applying religion inclusively will nuance a meaningful condition in creating “dialog” when fanaticism and claims on truth appear lately in this country